17th IEEE International Conference on Micro Electro Mechanical Systems. Maastricht MEMS 2004 Technical Digest
DOI: 10.1109/mems.2004.1290576
|View full text |Cite
|
Sign up to set email alerts
|

Pico liter dispenser with 128 independent nozzles for high throughput biochip fabrication

Abstract: This paper presents the development of the electrostatically dtiven inkjet-type dispenser for biochip printing. It has 128 independent reservoirs and the same number of nodes. It is designed based on SEAJet" printhead developed for the POS printer.SEAJet' technology is suitable for dispensing bio-chemical reagent, because there is no heat generation and no use of harmful material to hio chemical molecules. In addition to the SEAleta fabrication technology, a new process to fabricate micro through-holes and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Using this configuration, many droplets of different solutions can be dispensed simultaneously. For example, Takagi et al 81 developed a dispenser having 128 separate nozzles. Each nozzle is independently actuated by an electrostatically moving membrane, which generates a pressure pulse.…”
Section: Inkjet Printingmentioning
confidence: 99%
“…Using this configuration, many droplets of different solutions can be dispensed simultaneously. For example, Takagi et al 81 developed a dispenser having 128 separate nozzles. Each nozzle is independently actuated by an electrostatically moving membrane, which generates a pressure pulse.…”
Section: Inkjet Printingmentioning
confidence: 99%
“…Addressing N bits jets elements switch circuit system is using in inkjet chip. Logic functions integrated, enabling TIJ-based products have become increasingly high-end market [17][18][19][20][21][22][23]. Inkjet printers can put small number of DNA droplets (usually only a few picoliters, 10-12 l) accurately sprayed on to DNA glasses media.…”
Section: Introductionmentioning
confidence: 99%
“…Noncontact dispensing devices usually employ mechanical actuation to eject droplets through small nozzles. Presently, noncontact sys-tems utilize mainly the following actuation techniques: thermal actuation [4]- [6], pneumatic actuation [7], [8], electrostatic actuation [9], [10], acoustic actuation [11], [12], and piezoactuation [13]- [20]. There is a need for high-accuracy and highdensity microdroplet generators and for an understanding of the mechanics of droplet generators [14], [21]- [25].…”
Section: Introductionmentioning
confidence: 99%
“…Nakamura et al [26] showed that both piezoelectric and electrostatic actuation are suitable for biological sample printing. A number of research groups have presented piezoactuated [13]- [17] and electrostaticactuated [10] microdispensers for microarray printing. The piezoactuated dispensing head presented in this paper can be fabricated using low-cost microfabrication processes.…”
Section: Introductionmentioning
confidence: 99%